Teaching Experience, Psychological Capital and Work Engagement. Their Relationship with the Burnout on University Teachers - Mesurado, Belén (2019)
The present study has two objectives. The first one is to study whether the different stages of teacher professional development vary the levels of psychological capital, engagement and burnout on university teachers. On the other hand, the second objective is to study the relationship between the stages of professional development, psychological capital and engagement with the burnout of university teachers. The sample is intentional, not probabilistic and was composed of 250 university professors, with an average age of 39 years (M = 39.5 and a TD = 11.15); fifty one per cent of the participants were female. Thirty-eight per cent of the participants have been teaching at the university for five years or less; twenty seven per cent have been doing so for 6 to 10 years, and thirty five per cent have been teaching at the university for more than 11 years. To evaluate the variables, the Spanish versions of the Psychological Capital Questionnaire, Utrecht Work Engagement Scale and the Oldenburg Burnout Inventory were used. The results indicated that more experienced teachers have higher levels of psychological capital (specifically effectiveness, resilience and hope) and higher levels of absorption, an engagement dimension, than less experienced teachers. No significant differences were found in burnout levels linked to academic experience. Finally, psychological capital (specifically the dimensions of optimism and hope) as well as engagement (specifically the dimensions of vigor and dedication) inhibit the emergence of burnout on university teachers.